Draft Annual Plan 1994-95 Vol. III (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1994)
The condition of canal net work in the State including Lift Irrigation Projects is deteriorating and carrying capacity of the system already reduced substantially would reduce further. This scheme envisages restoring the capacity of lift pumps installed on various Lift Canal systems cons traction/remodeling of dilapidated bridges, construction of new minors or extension from the existing channels. Inclusion of this scheme in the 8th five year plan and annual plan is essentially required in order to fully utilize the irrigation potential already created in the commands of various projects which is in line with the guide-lines of the Planning Commission. Keeping in this requirement in view the Planning Department has includes this scheme in the '8th Five Year Plan making provision of Rs. 50 crore as recommended by working Group of Planning Commission and Rs. 96 lakhs has been spent during 1992 93.
Government of Haryana
Planning Department Government of Haryana
Keywords: Industries and Minerals; Electronics; Weights & Measures; Science & Technology; Non -Conventional Sources of Energy; Integrated Rural Energy Programme; Secretariat Economic Services; Census Survey & Statistics; Decentralized Planning; Tourism.